Impact of chronic kidney disease on health-related quality of life in adults: a systematic review and meta-analysis protocol - Amoah, William Wilberforce; Ihudiebube-Splendor, Chikaodili; Dzramado, Victor Luckyboy (Frontiers in Nephrology, 2025)
IntroductionChronic Kidney Disease (CKD) significantly impacts patients’ health-related quality of life (HRQoL), yet comprehensive evidence synthesis remains limited, particularly from African contexts. This systematic review aims to evaluate how CKD affects HRQoL in adult patients and identify the most impacted domains across disease stages, providing evidence to guide patient-centered care and health policy.MethodsFollowing PRISMA-P 2020 guidelines, we will systematically search PubMed, Embase, Scopus, Web of Science, Cochrane Library, and grey literature for observational studies and clinical trials evaluating HRQoL in adults (≥18 years) with CKD using validated instruments (SF-36, KDQOL, EQ-5D). Two independent reviewers will conduct study selection, data extraction, and quality assessment using the Newcastle-Ottawa Scale and Cochrane Risk of Bias Tool. Meta-analysis will be performed where feasible, with subgroup analyses by CKD stage, treatment modality, and geographic region.Expected outcomesThis review will provide nurses and clinicians with comprehensive evidence on HRQoL impairments across CKD stages, inform development of targeted psychosocial interventions, and guide resource allocation for holistic patient care. Findings will support healthcare providers in addressing not only physiological parameters but also patients’ subjective wellbeing and quality of life.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420251036629.